Ion-Mediated Recombination Dynamics in Perovskite-Based Memory Light-Emitting Diodes for Neuromorphic Control Systems - Yantara, Natalia (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2023 Wiley-VCH GmbH.